EXP-FUNCTION METHOD USING MODIFIED RIEMANN– LIOUVILLE DERIVATIVE FOR SINGULARLY PERTURBED BOUSSINESQ EQUATIONS OF FRACTIONAL-ORDER - Ul Hassan, Qazi Mahmood; Mohyud-Din, Syed Tauseef (Italian Journal of Pure and Applied Mathematics, 2014)
This paper witnesses the combination of an efficient transformation and Exp-function method to construct generalized solitary wave solutions of the nonlinear singularly perturbed sixth-order Boussinesq equations of fractional-order. Computational work and subsequent numerical results re-confirm the efficiency of proposed algorithm. It is observed that suggested scheme is highly reliable and may be extended to other nonlinear differential equations of fractional order.